MINAT DAN MOTIVASI SISWA EKSTRAKURIKULER SEPAK BOLA SMP KEMALA BHAYANGKARI I SUNGAI RAYA - Hutagaul Hutagaul; Victor G. Simanjuntak; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe background of this research is a lack of interest and motivation of students who follows the football extracurricular in SMP Kemala Bhayangkari I Sungai Raya. The purpose of this research is: to knowing and define how high the interst and motivation of students which following the football extracuricullar in SMP Kemala Bhayangkari I Sungai Raya. The research design used is descriptive-quantitative with survey method and data colletion technique used is questionnaire. The population of this research is grade VII, VIII, IX students of SMP Kemala Bhayangkari I who registeredin football extracurricular amounting 34 students of which 10 students were class VII, 18 students were class VIII and 6 were class IX. Sample of this research is 28 students of which 10 students from class VII and 18 student from class VIII.Sample selection using purpossive technique sampling. The results showed an interest of 28 students who participated in football extracurriclar in general is moderate. The following are: in a very low category amount 2 students (7.14%). In low category amount 3 sudents (10.71%). In a medium category amount 13 students (46.43%). In high category amount 6 students (21.43%) and in a very high category amount 4 students (14.29%). While the results of the motivation of 28 students who participated in football extracurricular in general is very high. With the following details: in a very low category amount 1 students (3.57%). In a low and medium category each amount 5 students (17.86%). In high category amount 8 students (28.57%) and in a very high category as many as 9 students (32.14%).Keyword: Interest, Motivation, Football Extracurricular